Kaneko Art '82 - '86. - Kaneko Art Gallery, Tokyo (Tokyo : Kaneko Art Gallery, 1986)
Yano, Michiko ; Suga, Kishio ; Hamada, Kiyoshi ; Kitamura, Hitoshi ; Matsutani, Takesada ; Kawamata, Tadashi ; Sugiura, Yasuyoshi ; Montonaga, Sadamasa ; Lee, U-Fan ; Tsuchitani, Takeshi ; Kamatani, Shinichi ; Iizuka, Hachiro ; Nils-Udo
Japans
boek